2007
DOI: 10.1111/j.1460-9568.2006.05275.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood–brain barrier permeability to large and small molecules following traumatic brain injury in mice

Abstract: The entry of therapeutic compounds into the brain and spinal cord is normally restricted by barrier mechanisms in cerebral blood vessels (blood-brain barrier) and choroid plexuses (blood-CSF barrier). In the injured brain, ruptured cerebral blood vessels circumvent these barrier mechanisms by allowing blood contents to escape directly into the brain parenchyma. This process may contribute to the secondary damage that follows the initial primary injury. However, this localized compromise of barrier function in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
161
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(167 citation statements)
references
References 38 publications
3
161
0
2
Order By: Relevance
“…123 Because S100B does not cross the intact BBB, its levels in the serum (or a serum/CSF ratio) have been proposed to be an indicator of barrier integrity. To investigate this possibility, Kirchhoff et al 124 evaluated S100B in the serum of severe TBI patients to determine if its levels correlated with the presence of albumin in the CSF.…”
Section: Blood Brain Barrier Compromisementioning
confidence: 99%
“…123 Because S100B does not cross the intact BBB, its levels in the serum (or a serum/CSF ratio) have been proposed to be an indicator of barrier integrity. To investigate this possibility, Kirchhoff et al 124 evaluated S100B in the serum of severe TBI patients to determine if its levels correlated with the presence of albumin in the CSF.…”
Section: Blood Brain Barrier Compromisementioning
confidence: 99%
“…Studies from our laboratory on a mouse model of focal TBI have recently demonstrated that at 1 to 2 h after injury there is extensive diffusion of intravenously injected horseradish peroxidase (a 40-kDa glycoprotein) in the pericontusional tissue, which by 4 h was no longer observed. 15 At 4 days post-injury, however, markers of smaller molecular weight (Ͻ10 kDa) continued to diffuse into the pericontusional cortex. Thus, the complete restoration of the barrier seems to require a time course that is much longer than that observed for large molecules.…”
Section: Introductionmentioning
confidence: 98%
“…Initial BBB opening in diffuse closed head injury is rapid and transient, beginning immediately after impact and closing within 30 min after impact 12 . However, there seems to be a size-selectivity issue at the BBB at sites of neural damage, during the early stages post-injury, with large molecules able to diffuse into the extravascular space in the short-term and smaller molecules able to diffuse for longer periods of time 13 . This has also been shown in cases of cytotoxic injury associated with the middle cerebral artery occlusion animal model of experimental stroke 14 .…”
mentioning
confidence: 99%